Assessment of the State of Platelet Haemostasis and Adhesive – Aggregation Properties of Platelets as a Factor of Increasing the Tendency to Thrombosis in Chronic Inflammation - Sokolovska, I. A.; Prybora, N.; Nechyporenko, V.; Pozdniakova, O.; Hordiienko, N.; Nechyporenko, K.; Siliavina, Yu.; Mavrin, V.; Kotuza, A.; Kliusov, O.; Kryachok, I.; Tytorenko, I.; et al. (My University, 2022)
In recent decades, considerable progress has been made in understanding the functional mechanisms of platelets and the correction of platelet haemostasis. Platelets are considered the most important participants in both the normal and pathological thrombotic processes characteristic of a variety of diseases and conditions. Alterations in various limbs of haemostasis are found in many somatic diseases (atherosclerosis, coronary heart disease, stroke), surgical procedures, oncological and immunological diseases. Inflammation underlies most diseases and remains an urgent problem in medicine. In the leukocyte infiltration of the inflammatory focus, the mechanism of its selfpreservation is of great importance. The activation of haematopoiesis during inflammation is triggered by factors released by stimulated leukocytes of the focus and peripheral blood. Therefore, the problem of the state of the haemostasis system should be the focus of constant attention of clinicians, and with the help of laboratory monitoring of the state of the haemostasis system, it is possible to carry out drug correction of the haemocoagulation potential.
Keywords: von Willebrand factor; adhesion; aggregation; platelets; thrombosis